GESTATIONAL DIABETES MELLITUS THROUGH THE LENS OF AYURVEDA: A COMPREHENSIVE REVIEW OF GARBHINI PRAMEHA WITH A CLINICAL CASE STUDY - Singapure Shraddha Arvind; Shruti Patil (World Journal of Advanced Research and Reviews, 2026)
Gestational diabetes mellitus (GDM) is typically defined as hyperglycemia that is diagnosed or develops during pregnancy. Gestational diabetes mellitus (GDM) is one of the most prevalent metabolic disorders complicating pregnancy and is associated with significant maternal, fetal, and long-term metabolic consequences. Despite advances in screening and management, GDM continues to pose challenges owing to its increasing prevalence and the lifelong risk of progression to type 2 diabetes mellitus in affected women, as well as adverse metabolic programming in the offspring. This article combines a comprehensive review of the current literature with a representative clinical case to provide an Ayurveda perspective on GDM. The review discusses the diagnosis of GDM from modern and Ayurveda concepts, antenatal evaluation, management strategies, maternal and fetal complications, preventive measures to improve pregnancy outcomes, postpartum strategies to reduce the future risk of diabetes, and the role of epigenetic changes in influencing long-term maternal and offspring health. The accompanying clinical case illustrates the practical application of these principles in patient care and highlights the value of obstetric management with Ayurveda principles. This combined approach aims to enhance the understanding of GDM, importance of early diagnosis and support comprehensive, evidence-informed management across the continuum of pregnancy and beyond.